Measuring COVID-19 health literacy and associated factors among caregivers in institutions for people with intellectual disabilities. - Lin, Jin-Ding; Lin, Lan-Ping (International Journal of Developmental Disabilities, 2025)
Objective: As Taiwan has become a super-aged society, care institutions for people with disabilities, where most residents are from vulnerable groups, must implement measures against emerging infectious diseases. This study analyzed COVID-19 health literacy and associated factors of caregivers in institutions for people with intellectual disabilities. Methods: Purposive sampling was employed to select 382 institutional caregivers from eight care institutions for people with intellectual disabilities. A structured questionnaire, the COVID-19 Health Literacy Assessment Scale, was used as the measurement instrument. The scale is a self-designed questionnaire comprising 21 items on health literacy and COVID-19 prevention policies. The questionnaire responses were documented using Microsoft Excel and analyzed using SPSS 23.0 through descriptive and inferential statistical analyses. Results: The participants had a mean COVID-19 health literacy score of 88.8 ± 8.9 (range: 63–105). There was a significant correlation between the three dimensions of COVID-19 health literacy, namely 'ability to obtain COVID-19-related information,' 'ability to understand COVID-19-related information,' and 'ability to distinguish and apply COVID-19-related information.' Multiple logistic regression analysis of the relationships between the demographic variables and COVID-19 health literacy revealed 'monthly service hours' as a significantly correlated factor. Participants who worked less than 160 h per month had higher COVID-19 health literacy than those who worked 160 h or more monthly (OR = 1.922; 95% CI = 1.183–3.122). Conclusions: This study recommends that institutions for people with intellectual disabilities establish comprehensive pandemic prevention policies according to the level of health literacy among staff members to effectively improve their COVID-19 health literacy and response strategies, reduce health risks of caregivers and patients, and ensure health and well-being in the institutional community.